2008
DOI: 10.1149/1.2898714
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Noble Metals into Ordered Macropores in p-Type Silicon

Abstract: The electrodeposition of noble metals, i.e., platinum, palladium, and gold, into macroporous p-type silicon was examined. For platinum and palladium, the electrodeposition proceeded preferentially from the pore bottom to the opening when sodium chloride was used as a supporting electrolyte. When sodium sulfate was used as a supporting electrolyte, the electrodeposition mainly proceeded at pore openings, leading to plugging. For gold electrodeposition, a condition for achieving pore filling from the bottom was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
66
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 29 publications
2
66
0
2
Order By: Relevance
“…Electro-deposition of Au, Pt and Pd into macro-pores has been studied [20,21]. It has shown that macro-porous silicon filling with Pd and Pt starts growing from the pore bottom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electro-deposition of Au, Pt and Pd into macro-pores has been studied [20,21]. It has shown that macro-porous silicon filling with Pd and Pt starts growing from the pore bottom.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the electro-deposition process is well described in the literature [16,17,20,21], the physical properties of the obtained compound depend on fixed parameters of the sample preparation including the chemical nature of the semiconductor, crystal orientation, doping type and density, electrolyte composition and applied current or voltage. Systematic investigations with different electro-deposition parameters are required in order to find new and better physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,6 The filling with magnetic materials allows the tuning of the resulting magnetic properties of the composite system.…”
mentioning
confidence: 99%
“…Recently, electrodepositions of Pt, Pd, and Au in the dark have been conducted. We have investigated many factors which influence the electrodeposition behavior, such as electrolysis conditions, compositions of electrolyte, nucleation, diffusion and reaction rates [6]. In this study, we focused on the relationship between the nucleation by immersion plating and electrodeposition behavior.…”
mentioning
confidence: 99%
“…In the case of Pt, the amount of deposition in immersion plating is very small. Short time electrodeposition of Pt showed that deposition occurred only at the pore bottoms in the initial stages, and thus deposits grew from the bottoms [6]. When we consider the reason why deposition occurs preferentially at the pore bottoms, we cannot neglect the current flow path.…”
mentioning
confidence: 99%